Renin-angiotensin system gene polymorphisms and high blood pressure in Lithuanian children and adolescents - Sandrita Simonyte; Renata Kuciene; Jurate Medzioniene; Virginija Dulskiene; Vaiva Lesauskaite (BMC, 2017)
Abstract Background Epidemiological studies have demonstrated the influence of environmental factors on HBP in the population of Lithuanian children, although the role of genetic factors in hypertension has not yet been studied. The aim of this study was to assess the distribution of AGTR1, AGT, and ACE genotypes in the Lithuanian child population and to determine whether these genotypes have an impact on HBP in childhood. Methods This cross-sectional study enrolled 709 participants aged 12-15 years. The subjects were genotyped for AGT (M235 T, rs699), AGTR1 (A1166C, rs5186), and ACE (rs4340) gene polymorphisms using real-time and conventional polymerase chain reactions. Blood pressure and anthropometric parameters were measured. Results The prevalence of HBP was 38.6% and was more frequently detected in boys than in girls (47.9% vs. 29.5%; p < 0.001). No significant differences in the frequencies of the AGT or AGTR1 genotypes or alleles between boys and girls were observed, except for ACE genotypes. The mean SBP value was higher in HBP subjects with ACE ID genotype compared to those with ACE II homozygotes (p = 0.04). No significant differences in BP between different AGT and AGTR1 genotype groups were found. Boys who carried the ACE ID + DD genotypes had higher odds of having HBP than carriers of the ACE II genotype did (controlling for the body mass index (BMI): ORMH = 1.83; 95% CI, 1.11-3.02, p = 0.024; and controlling for waist circumference (WC): ORMH = 1.76; 95% CI, 1.07-2.92, p = 0.035). These associations were not significant among girls. The same trend was observed in the multivariate analysis - after adjustment for BMI and WC, only boys with ACE ID genotype and ACE ID + DD genotypes had statistically significantly increased odds of HBP (aOR = 2.05; 95% CI, 1.19-3.53 (p = 0.01) and aOR = 1.82; 95% CI, 1.09-3.04 (p = 0.022), respectively). Conclusions The evaluated polymorphisms of the AGT and AGTR1 genes did not contribute to the presence of HBP in the present study and may be seen as predisposing factors, while ACE ID genotypes were associated with significantly increased odds for the development of HBP in the Lithuanian child and adolescent population - especially in boys.